SPECIATION OF TIN (SN2+ AND SN4+) IN AQUEOUS CL SOLUTIONS FROM 25°C TO 350°C: AN IN SITU EXAFS STUDY - Sherman D.M.; Ragnarsdottir K.V.; Oelkers E.H.; Collins C.R. (My University, 2000)
X-ray absorption fine structure spectroscopic (EXAFS) measurements were made of tin chloride solutions at temperatures from 25°C to 350°C. In Cl concentrations of 0.5 to 2.5 M, aqueous tin(II) forms SnCln2-n complexes with n increasing from 3.4 at 25°C to 3.9 at 250°C, indicating the presence of SnCl3- and SnCl42-. Between 250°C and 350°C, SnCl42- is the dominant species. In oxidized Cl brines, aqueous tin(IV) occurs as the SnCl62- complex from 25°C to 250°C. Neither the SnCl42- nor the SnCl62- complexes have been previously observed. The existence of these complexes, however, implies that SnO2 will be much more soluble than predicted by previous geochemical models. In particular, oxidized acidic brines will be capable of transporting tin as tin(IV) complexes.
Keywords: TIN; CL SOLUTIONS; EXAFS